Contrasting effects of temperature and winter mixing on the seasonal and inter-annual variability of the carbonate system in the Northeast Atlantic Ocean - C. Dumousseaud; E. P. Achterberg; T. Tyrrell; A. Charalampopoulou; U. Schuster; M. Hartman; D. J. Hydes (Biogeosciences, 2010)
Future climate change as a result of increasing atmospheric CO2 concentrations is expected to strongly affect the oceans, with shallower winter mixing and consequent reduction in primary production and oceanic carbon drawdown in low and mid-latitudinal oceanic regions. Here we test this hypothesis by examining the effects of cold and warm winters on the carbonate system in the surface waters of the Northeast Atlantic Ocean for the period between 2005 and 2007. Monthly observations were made between the English Channel and the Bay of Biscay using a ship of opportunity program. During the colder winter of 2005/2006, the maximum depth of the mixed layer reached up to 650 m in the Bay of Biscay, whilst during the warmer (by 2.6 ± 0.5 °C) winter of 2006/2007 the mixed layer depth reached only 300 m. The inter-annual differences in late winter concentrations of nitrate (2.8 ± 1.1 μmol l−1) and dissolved inorganic carbon (22 ± 6 μmol kg−1, with higher concentrations at the end of the colder winter (2005/2006), led to differences in the dissolved oxygen anomaly and the chlorophyll α-fluorescence data for the subsequent growing season. In contrast to model predictions, the calculated air-sea CO2 fluxes (ranging from +3.7 to −4.8 mmol m−2 d−1) showed an increased oceanic CO2 uptake in the Bay of Biscay following the warmer winter of 2006/2007 associated with wind speed and sea surface temperature differences.